An Emotion-Based Perspective on Risk Assessment: The SOR Model for Operators - Parlak, Turgay; Ozkan, Coskun (SAGE PUBLICATIONS INC, 2026)
The aim of this study is to examine the emotional effects of stimuli present in the work environment on employee behavior. The study utilized the stimulus-organism-response (SOR) model and included 182 operators from a designated production area. Content, construct, and reliability validity assessments were performed on the instruments measuring the active elements of stimuli and responses. The Pleasure-Arousal-Dominance (PAD) Scale was employed to assess emotional state (organism), with attention to cultural and linguistic validity. Simple and multiple regression analyses were conducted to test the proposed hypotheses. Of the participants, 43% were vocational high school graduates, and 82% had more than 10 years of operator experience. Results indicated that 83% perceived stimuli, 45% reported positive emotional states while working, and 70% responded to stimulus factors. Stimuli exerted a significant effect on emotional state, whereas emotional state did not significantly influence reactions. Additionally, stimuli had a positive, significant effect on observed reactions. Further investigation into workplace stimuli and a broader evaluation of how employee emotional states impact work life may offer valuable contributions to occupational health and safety research.
Keywords: occupational safety; risk assessment; work accident; SOR model; emotions; PAD model; PSYCHOSOCIAL SAFETY CLIMATE; OCCUPATIONAL ACCIDENTS; WORK ENVIRONMENTS; JOB-SATISFACTION; FIT INDEXES; BEHAVIOR; STIMULUS; HEALTH; PERCEPTION; COVID-19; Social Sciences - Other Topics